The anatomical structure of the leaves in Echeveria sp. - Deluciana, Chelsea Novalin; Ermayanti, Ermayanti; Susanti, Rahmi (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2023)
.